Beyond Passive Immunity: Is There Priming of the Fetal Immune System Following Vaccination in Pregnancy and What Are the Potential Clinical Implications? - Wilcox, Christopher R.; Jones, Christine E. (Frontiers in Immunology, 2018)
Infection is responsible for over half a million neonatal deaths worldwide every year, and vaccination in pregnancy is becoming increasingly recognised as an important strategy for the protection of young infants. Increasing evidence suggests that exposure to maternal infection in utero may ‘prime’ the developing immune system, even in the absence of infant infection. It is also possible that in utero priming may occur following maternal vaccination, with antigen-specific cellular immune responses detectable in utero and at birth. However, this remains a topic of some controversy. This review focusses on the evidence for in utero priming and the clinical implications for vaccination in pregnancy, considering whether in utero priming following vaccination could provide protection independent of antibody-mediated passive immunity, the possible effects of vaccination on subsequent infant vaccinations, their potential ‘non-specific’ effects, and how the design and timing of vaccination might affect prenatal priming. Looking forwards, we describe other possible options for quantifying antigen-specific cellular responses, including MHC tetramers, novel proliferation and cytokine-based assays, and animal models. Together, these may help us address future research questions and establish more robust evidence of fetal immune system priming.